Prevalence of asymptomatic nephrolithiasis amongst prospective living kidney donors - Uzodimma E., Onwuasoanya; Olatise O., Olalekan; Agrawal K., Rajesh; Obiatuegwu O., Kenechukwu; Ekwuazi O. , Hyginus (International Surgery Journal, 2024)
Background: About 12% of men and 5% of women will develop symptomatic nephrolithiasis during their lifetime. Symptomatic nephrolithiasis is linked to many systemic conditions such as metabolic syndrome, chronic kidney disease and hyperparathyroidism. Not much is known about the prevalence of nephrolithiasis in asymptomatic patients as well as their association with systemic conditions seen in the symptomatic subset. Methods: This is a retrospective study of all prospective living kidney donors who presented to Zenith Medical and Kidney Centre, Abuja, Nigeria between January 2022 and December 2022. Relevant information was retrieved from the institution’s computer database, entered in a structured proforma and analyzed with SPSS version 25.0. Results were reported in percentages, mean±standard deviation. Results: A total of 133 patients were recruited for the study, the age range was 18-52 years with mean age of 27.47 years and standard deviation of 6.8. The male to female ratio was 15.6:1. The body mass was greater than 30 kg/m2 in 4.8% of patients. Hypertension was found in 5.3% while urinary tract infection was found in 24.1% of the patients. Nephrolithiasis was seen in 5.3% of the patients, with size ranging from 2.14mm to 9.4mm, the stone was bilateral in 0.8% of the patients. Conclusions: The prevalence of asymptomatic nephrolithiasis amongst prospective kidney donors is 5.3%. Asymptomatic kidney stone formers have different demographic characteristics and lack the co-morbidities described in symptomatic kidney stone formers.